Comparing antiretroviral treatment outcomes between a prospective community-based and hospital-based cohort of HIV patients in rural Uganda - Kipp, Walter; Konde-Lule, Joseph; Rubaale, Tom; Okech-Ojony, Joa; Alibhai, Arif; Saunders, Duncan L. (BMC international health and human rights, 2011)
Improved availability of antiretroviral therapy in sub-Saharan Africa is intended to benefit all eligible HIV-infected patients; however in reality antiretroviral services are mainly offered in urban hospitals. Poor rural patients have difficulty accessing the drugs, making the provision of antiretroviral therapy inequitable. Initial tests of community-based treatment programs in Uganda suggest that home-based treatment of HIV/AIDS may equal hospital-based treatment; however the literature reveals limited experiences with such programs.
Keywords: Primary Health Care Service; District Health Management Team; Successful Treatment Outcome; Unpaid Volunteer; Hospital Cohort